Pengembangan kamus daring bahasa Prancis-Indonesia bidang pariwisata berbasis blog interaktif - Setia Rini; Nani Kusrini (Aksara: Jurnal Bahasa dan Sastra, 2020)
The industrial revolution 4.0 has given many great impacts in all aspects, either positive or negative. In areas of education, there are many things that have changed, it is more modern and efficient thanks to technology, there is no limitation of time and place. The learning process at all levels has already used various innovative learning media and digital media. In addition, the use of the Internet for learning and teaching purposes is used more from time to time. In this era, all things integrate with the internet (internet of things), this condition then stimulates all people to be more creative to take advantage of the internet in the way of producing or creating a creation. This can be used by many people like the application, the site, the web, etc. Consequently, based on the previous research, we therefore make a development of our research result to be more efficient, more modern and which is suitable with the condition of the era. The French-Indonesian digital dictionary on tourism in 2018, we are developing it by adding more data and also applications for all users. We therefore hope that this digital dictionary can help and be used by many people who learn French, especially in the field of tourism.